A Comparison of Clinical Outcomes and Complication Rates in Open Versus Minimally Invasive Achilles Tendon Repair Using PROMIS Scores. Issue 4 (22nd October 2020) - Caolo, Kristin C.; Eble, Stephanie K.; Elliott, Andrew J.; Demetracopoulos, Constantine A.; Deland, Jonathan T.; Drakos, Mark C.; Ellis, Scott J.
Category: Sports Introduction/Purpose: While there is no current consensus on whether to use an open or minimally invasive (MIS) approach for Achilles tendon repair after acute rupture, there is a recent trend towards decreasing complication rates for both procedures as well as favorable clinical outcomes. While many studies have compared complication rates between these procedures, no study has examined differences in clinical outcomes using PROMIS scores with a large cohort of patients. PROMIS has been validated for use in assessing outcomes following Achilles repair and allows for evaluation of surgical outcomes compared to population means. We hypothesized that patients in both open and MIS groups would have improved PROMIS scores postoperatively, but that there would be minimal differences in PROMIS scores and complication rates between surgical techniques. Methods: 228 patients were identified who underwent surgery for acute unilateral Achilles tendon repair between January 2016 and December 2018. Nine surgeons were represented. The open repair group was defined by a larger incision (>4 cm) and no use of a commercially available minimally invasive device. The minimally invasive group was defined by a smaller incision (<3.5 cm) and use of the device. Postoperative protocols were similar between groups. Preoperative and postoperative PROMIS scores were collected prospectively through our institution's registry; all domains have a population mean of 50. 147 patients completed PROMIS at minimum 1 year postoperatively, 50 in the open repair group and 97 in the MIS group. PROMIS scores were compared between procedures using t-tests with a significance level of 0.05. A chi-square test of independence was also performed to analyze the relationship between complications and procedure type. Results: No significant differences in postoperative PROMIS scores were observed between the open and MIS repair groups. Average postoperative PROMIS scores included: Physical Function (54.92 MIS, 57.25 Open, p=0.123); Pain Interference (45.00 MIS, 45.63 Open, p=0.600); and Pain Intensity (34.97 MIS, 35.21 Open, p=0.812). There were also no significant differences in complication rates between groups. 20.6% of patients in the MIS group had at least one postoperative complication (9.3% DVT, 4.1% rerupture, 2% sural nerve injury, 2% infection), compared to 18.0% in the open group (8% DVT, 2% rerupture, 2% sural nerve injury, 0% infection) (p=0.705). Conclusion: Patients undergoing minimally invasive and open Achilles tendon repair after acute rupture have similar clinical outcomes and complication rates. Though this study did not consider outcomes such as postoperative pain levels and level of sport or return to sport, it demonstrates that patients undergoing Achilles tendon rupture regardless of technique have very favorable PROMIS scores compared to population means. This information is important for surgeons choosing which procedure to use as both are safe and effective techniques for repairing the Achilles tendon.